Logistical mobility in plateaus in Central-Western Santa Cruz, Argentina. An approach from technological, archaeofaunal and anthracological evidence - Pasqualini, Sebastian Diego (2016)
The aim of this work is to discuss hunter-gatherers´ logistical mobility strategies in Central-Western Santa Cruz province during the last 2500 years BP, in a context of human adaptations to semi-desert conditions. The approach to the archaeological record is focused on integrating three independent lines of evidence, technology, archaeofauna and anthracology. Logistical mobility will be addressed focusing on two main aspects: resources transportation and variability of archaeological contexts. The observed variability has allowed shedding light on the use of the category "logistical" used to describe plateaus. Additionally, these areas show a well-planned and scheduled use during a regional process of desiccation.